2021
DOI: 10.3390/pharmaceutics13111912
|View full text |Cite
|
Sign up to set email alerts
|

Annatto Oil Loaded Nanostructured Lipid Carriers: A Potential New Treatment for Cutaneous Leishmaniasis

Abstract: Annatto (Bixa orellana L.) is extensively used as food pigment worldwide. Recently, several studies have found it to have healing and antioxidant properties, as well as effective action against leishmaniasis. Therefore, the purpose of this study was to incorporate the oil obtained from annatto seeds into a nanostructured lipid carrier (NLC) and evaluate its physicochemical properties and biological activity against Leishmania major. Nanoparticles were prepared by the fusion-emulsification and ultrasonication m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 90 publications
(120 reference statements)
2
8
0
Order By: Relevance
“…In addition, the results showed that the long and short spacing of the crystalline lattice were modified in the hybrid systems when compared to the lipid raw materials (CP and MM), where a reduction in peak intensity was observed, and this can be related to the reduction in the degree of crystallinity of the lipid in its nanoparticulate state, resulting in a more amorphous system ( Table 2 ). Similar results were observed by Ferreira et al, [ 42 ] without the presence of laponite.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, the results showed that the long and short spacing of the crystalline lattice were modified in the hybrid systems when compared to the lipid raw materials (CP and MM), where a reduction in peak intensity was observed, and this can be related to the reduction in the degree of crystallinity of the lipid in its nanoparticulate state, resulting in a more amorphous system ( Table 2 ). Similar results were observed by Ferreira et al, [ 42 ] without the presence of laponite.…”
Section: Resultssupporting
confidence: 91%
“…Figure 2 shows the profile for the loss of mass during heating of the components of the systems ( Figure 2 a) and hybrid systems ( Figure 2 b,c). Figure 2 a shows similar results for loss of mass of the crystalline solids (PL bulk , MM bulk , and CP bulk ) in a single event, and these results agree with Ferreira et al, 2021 [ 42 ]. Laponite, in turn, had its mass reduced by 7.6% between 33 °C and 79 °C due to the loss of adsorption water and 4.3% slowly over the maximum heating period, due to the loss of interlamellar clay water.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations